Physiological and metabolic responses to a hill walk. - Ainslie, P; Campbell, I; Frayn, K; Humphreys, S; Maclaren, D; Reilly, T (2002)
The physiological and metabolic demands of hill walking have not been studied systematically in the field despite the potentially deleterious physiological consequences of activity sustained over an entire day. On separate occasions, 13 subjects completed a self-paced hill walk over 12 km, consisting of a range of gradients and terrain typical of a mountainous walk. During the hill walk, continuous measurements of rectal (T(re)) and skin (T(sk)) temperatures and of respiratory gas exchange were made to calculate the total energy expenditure. Blood samples, for the analysis of metabolites and hormones, were taken before breakfast and lunch and immediately after the hill walk. During the first 5 km of the walk (100- to 902-m elevation), T(re) increased (36.9 +/- 0.2 to 38.5 +/- 0.4 degrees C) with a subsequent decrease in mean T(sk) from this time point. T(re) decreased by approximately 1.0 degrees C during a 30-min stop for lunch, and it continued to decrease a further 0.5 degrees C after walking recommenced. The total energy intake from both breakfast and lunch [5.6 +/- 0.7 (SE) MJ] was lower than the energy expended [14.5 +/- 0.5 (SE) MJ; P < 0.001] during the 12-km hill walk. Despite the difference in energy intake and expenditure, blood glucose concentration was maintained. The major source of energy was an enhanced fat oxidation, probably from adipose tissue lipolysis reflected in high plasma nonesterified fatty acid concentrations. The major observations were the varying thermoregulatory responses and the negative energy balance incurred during the hill walk. It is concluded that recreational hill walking can constitute a significant metabolic and thermoregulatory strain on participants.